2018
DOI: 10.1080/03007995.2018.1551192
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of persistence and adherence between fixed-dose combinations and two-pill combinations in Japanese patients with type 2 diabetes

Abstract: Objective: To compare treatment patterns, persistence and adherence between fixed-dose combinations (FDCs) and two-pill combinations (TPCs) of oral antidiabetic drug (OAD) classes in Japanese patients with type 2 diabetes mellitus (T2DM) using administrative claims databases (Japan Medical Data Center [JMDC] and Medical Data Vision [MDV]). Methods: This was a retrospective, longitudinal cohort analysis conducted between 2011 and 2015, in patients with T2DM receiving OADs as FDC or TPC. Outcomes included prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
(23 reference statements)
1
11
1
Order By: Relevance
“…Our findings are generally consistent with those of previous studies that showed a positive association between FDC therapy and adherence and persistence 11,12,21‐24 . A meta‐analysis conducted by Bangalore et al revealed that FDC therapy improved medication non‐compliance by 26% (pooled relative risk, 0.74; 95% CI 0.69‐0.80; P < .0001) when compared with a free‐drug combination 21 .…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are generally consistent with those of previous studies that showed a positive association between FDC therapy and adherence and persistence 11,12,21‐24 . A meta‐analysis conducted by Bangalore et al revealed that FDC therapy improved medication non‐compliance by 26% (pooled relative risk, 0.74; 95% CI 0.69‐0.80; P < .0001) when compared with a free‐drug combination 21 .…”
Section: Discussionsupporting
confidence: 91%
“…With one exception from Greece [ 19 ], there is little evidence on outcomes in European health care markets, which differ considerably from the US health care sector, e.g., with respect to drug reimbursement policies that may affect medication adherence. A further weakness of most of the previous studies is their short follow-up period of no more than 12 months [ 11 17 , 19 , 20 ]. Literature on medication compliance suggests that long-term compliance is more difficult to obtain than short-term compliance and requires a combination of interventions to be effective [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of medications and the complexity of the regimen may also affect adherence to treatment 11,20,33 . For example, fixeddose combinations are associated with greater persistence and adherence than two-pill combinations 34 .…”
Section: Discussionmentioning
confidence: 99%